PENGARUH STIMULASI PERMAINAN MIND MAPPING TERHADAP FUNGSI KOGNITIF PADA ANAK USIA 4-6 TAHUN DI DESA ULLATH KECAMATAN SAPARUA - Silvianovelista R Losoiyo (Pasapua Health Journal, 2021)
Introduction: Cognitive abilities are the basis for a child’s ability to think. Cognitive is a thought process, namely the ability of individuals to connect, assess, and consider an incident or events. So the cognitive process is related to the level of intelligence (intelligence) which marks a person with various interests especially aimed at learning ideas. Method: The research conducted was a pre-experimental study with a one group pre-test and post-test design approach .The population is a generalization area consisting of objects or subjects that have certain qualities and characteristics determined by the researcher to be studied and then drawn conclusions. ). The population in this study were children in the community of Ullath Village, Saparua District, totaling 35 children. The sample is a small part of the total population of children (4-6) years with a total of 35 respondents owned and used for research. Results: There is a stimulating effect of mind mapping games on cognitive function in children aged 4-6 years (p = 0.000) in Ullath Village, Saparua District. Conclusion: The simulation games can affect the cognitive development of children aged 4-6 years for the better